The Classical World : An Epic History from Homer to Hadrian - Lane Fox, Robin (London Penguin Books, 2006)
Chronicles the history and development of the classical civilizations of Greece and Rome, exploring each group's art, architecture, literature, philosophy, and politics and explaining the role they played in the creating the foundations of Western civilization.
Include Index
Keywords: Civilization, Classical -- Civilization, Greco-Roman -- Mediterranean Region